Sub-Micromolar Inhibition of SARS-CoV-2 3CLpro by Natural Compounds - Bruno Rizzuti; Laura Ceballos-Laita; David Ortega-Alarcon; Ana Jimenez-Alesanco; Sonia Vega; Fedora Grande; Filomena Conforti; Olga Abian; Adrian Velazquez-Campoy (MDPI AG, 2021)
Inhibiting the main protease 3CLpro is the most common strategy in the search for antiviral drugs to fight the infection from SARS-CoV-2. We report that the natural compound eugenol is able to hamper in vitro the enzymatic activity of 3CLpro, the SARS-CoV-2 main protease, with an inhibition constant in the sub-micromolar range (Ki = 0.81 μM). Two phenylpropene analogs were also tested: the same effect was observed for estragole with a lower potency (Ki = 4.1 μM), whereas anethole was less active. The binding efficiency index of these compounds is remarkably favorable due also to their small molecular mass (MW < 165 Da). We envision that nanomolar inhibition of 3CLpro is widely accessible within the chemical space of simple natural compounds.